Improving speaking ability using English "Shock Day" approach - Geminastiti Sakkir; Zulfirman; Nurlaelah Mahmud; Jamaluddin Ahmad (International Journal of Humanities and Innovation (IJHI), 2020)
The aim of this study was to measure the effectiveness of English "Shock Day" to improve university students' speaking ability. It employed a quantitative method using the pre-experimental design. The subject of the research was the fourth-semester students in one of the private universities in South Sulawesi, Indonesia, in the academic year of 2018/2019. The total population of this research was 76 students. The total number of the sample was 25 students were taken by cluster sampling technique. The instrument was a speaking test to obtain data on the students' speaking achievement through the implementation of English shock day. The data analysis found that the students' mean score in English speaking was significantly improved. The students' mean score in the pretest was 58.36, while their mean score in the posttest was 70.68. The t-table was also lower than the t-test, that is 2.093 < 6.650. Based on the result, the researchers concluded that the implementation of English shock day improved students' ability to speak.